Therapeutic Potential of Curcumin in Modulating the HMGB1/TLR4/NF-κB Axis in Polymicrobial Peritonitis: A Systematic Review and Dose-Response Meta-Analysis - Leonardo Aaron Hartanto; Neni Susilaningsih; Erik Prabowo (HM Publisher, 2026)
Background: Polymicrobial peritonitis and its systemic sequela, sepsis, represent a catastrophic dysregulation of the host immune response to infection, leading to multiple organ dysfunction syndrome and high mortality rates. The pathophysiology is driven by a hyperinflammatory cytokine storm followed by immunoparalysis, governed centrally by the high mobility group box 1 (HMGB1)/toll-like receptor 4 (TLR4)/nuclear factor-kappa B (NF-κB) signaling axis. Curcumin, a polyphenolic compound derived from Curcuma longa, has demonstrated potent immunomodulatory properties. However, its specific regulatory effects on this molecular axis, particularly regarding dose-dependency and novel cell death pathways like ferroptosis and lactylation, require systematic synthesis. Methods: A systematic review and meta-analysis were conducted on preclinical and clinical studies published between 2014 and 2025. Ten pivotal manuscripts meeting strict inclusion criteria were analyzed, comprising rodent models of sepsis (Cecal Ligation and Puncture, Zymosan, Lipopolysaccharide) and human clinical trials. Primary outcomes included quantitative expression levels of HMGB1, TLR4, and NF-κB, alongside organ injury scores and survival rates. Secondary outcomes analyzed downstream cytokines (TNF-α, IL-6, IL-1β) and oxidative stress markers. Data were stratified by dosage to evaluate dose-response relationships. Results: The analysis included data from 218 subjects. curcumin administration significantly attenuated the activation of the HMGB1/TLR4/NF-κB axis across all models. Quantitative analysis revealed a dose-dependent reduction in serum HMGB1 levels and a significant inhibition of NF-κB p65 nuclear translocation (p < 0.001). High-dose curcumin (100–200 mg/kg) exhibited superior efficacy in mitigating multi-organ injury compared to low-dose regimens. Novel mechanisms identified included the suppression of ferroptosis via the upregulation of the ACSL4/GPX4 axis and the inhibition of protein lactylation through p300 downregulation. Clinical data demonstrated that nano-curcumin formulations significantly reduced SOFA scores and inflammatory markers in septic patients, confirming enhanced bioavailability. Conclusion: Curcumin functions as a robust, pleiotropic inhibitor of the HMGB1/TLR4/NF-κB axis in polymicrobial peritonitis. Its therapeutic efficacy is dose-dependent and involves the regulation of emerging epigenetic and cell death pathways. These findings support the clinical integration of nano-curcumin as an adjuvant therapy for surgical sepsis.